EKSPERIMENTASI MODEL PEMBELAJARAN THINK TALK WRITE DAN NUMBERED HEAD TOGETHER DENGAN PENDEKATAN SAINTIFIK DISERTAI STRATEGI PETA KONSEP PADA MATERI BILANGAN DITINJAU DARI GAYA BERPIKIR SISWA KELAS VII SMPN Se-KOTA METRO LAMPUNG TAHUN PELAJARAN 2014/2015 - Fitriani, Nur Syarifah; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: This research aimed to know: (1) which one of the learning models with scientific approach gave a better achievement between TTW-Concept Mapping, NHT- Concept Mapping, or classical, (2) which one of the students with thinking style had a better achievement between students with concrete sequential, abstract sequential, concrete random, or abstract random, (3) at each of learning models with scientific approach, which one of the students with thinking style had a better achievement between students with sequential concrete, sequential abstract, concrete random, or abstract random, (4) at each thinking style, which one of learning models with scientific approach gave a better achievement between TTW-Concept Mapping, NHT- Concept Mapping, or classical. Population of the research was the seventh class students of Junior High School at Metro city on academic year 2014/2015. Instrument used to gather data were mathematics achievement test and thinking style questionnaire. Data analysis technique used was unbalanced two ways analysis of variance. Based on the data analysis, it was concluded as follows. 1) TTW-CM gave better achievement than NHT-CM, NHT-CM gave better achievement than classical, 2) Students with concrete sequential had better achievement than students with abstract sequential, concrete random, and abstract random, students with abstract sequential gave the same achievement with concrete random, and abstract random, student with concrete random gave the same achievement with abstract random, 3) In each learning models, student with concrete sequential had better achievement than students with abstract sequential, concrete random, and abstract random. Students with abstract sequential had better achievement than students with concrete random, and abstract random, the student with concrete random gave the same achievement with abstract random, 4) In each of thinking style, students who was subject to TTW-CM models gave better achievement than NHT-CM, NHT-CM gave better achievement than classical.Keywords: Think Talk Write, Numbered Head Together, Thinking Style, Achievement.Â